2012
DOI: 10.46989/001c.20656
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Protein Level on Growth Performance and Nitrogen Excretion of the Yellow Tail Cichlid, Pseudotropheus acei

Abstract: As from January 2010 The Israeli Journal of Aquaculture-Bamidgeh (IJA) will be published exclusively as an on-line Open Access (OA) quarterly accessible by all AquacultureHub (http://www.aquaculturehub.org) members and registered individuals and institutions. Please visit our website (http://siamb.org.il) for free registration form, further information and instructions. This transformation from a subscription printed version to an on-line OA journal, aims at supporting the concept that scientific peer-reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In Wuchang bream (Megalobrama amblycephala), the weight gain (WG) and muscle protein content were significantly increased, while the feed conversion ratio (FCR) and muscle lipid content were significantly reduced as dietary protein level increased from 30% to 34% [2]. However, high dietary protein level increased the feed costs [3] and ammonia emissions [4]. Güroy et al [4] found that increasing dietary protein level from 35% to 50% significantly increased the ammonia emissions in yellow tail cichlid (Pseudotropheus acei).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Wuchang bream (Megalobrama amblycephala), the weight gain (WG) and muscle protein content were significantly increased, while the feed conversion ratio (FCR) and muscle lipid content were significantly reduced as dietary protein level increased from 30% to 34% [2]. However, high dietary protein level increased the feed costs [3] and ammonia emissions [4]. Güroy et al [4] found that increasing dietary protein level from 35% to 50% significantly increased the ammonia emissions in yellow tail cichlid (Pseudotropheus acei).…”
Section: Introductionmentioning
confidence: 99%
“…However, high dietary protein level increased the feed costs [3] and ammonia emissions [4]. Güroy et al [4] found that increasing dietary protein level from 35% to 50% significantly increased the ammonia emissions in yellow tail cichlid (Pseudotropheus acei).…”
Section: Introductionmentioning
confidence: 99%
“…So far many of the ornamental fish traders have been using shrimp feeds or other fish feeds meant for rearing the food fishes. Therefore, development of species specific ornamental fish diet as per the nutrient requirement of fish is one of the priority areas in fish nutrition research [31,32]. Among freshwater ornamental fish, blue gourami, Trichogaster trichopterus is an important sought after ornamental fish.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it should be carefully formulated to meet the nutrient requirements (Sui et al, 2015). Other advantages associated with an optimized dietary protein level include rapid and cost-effective growth, reduced environmental impact, and improved water quality (Guroy et al, 2012). Fishmeal is the most common and expensive protein source used in aqua feed formulations.…”
Section: Introductionmentioning
confidence: 99%